Stereonet structure

CN123022847APending Publication Date: 2026-10-30TOYOBO MC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580023900.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-03-10
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0017]本发明的立体网状结构体的制法比较简单,并且能够得到减小表皮层的表观密度而比以往轻量、但具有优异的缓冲性能的立体网状结构体。通过使用本发明的立体网状结构体,能够在各种用途中实现轻量化,其结果,能够期待环境负荷的降低。另外,除了由轻量化带来的环境负荷的降低以外,在作为寝具使用时能够使寝具轻量化,因此也能够减轻搬运的负荷,在作为铁道/汽车/二轮车等的车辆用座位使用的情况下能够使车身质量轻量化,因此也能够降低车辆行驶时所需的能量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

Provided is a three-dimensional network structure which is lightweight while having excellent cushioning performance. A three-dimensional network structure characterized by being composed of continuous lines composed of a thermoplastic resin composition, having a three-dimensional random loop bonding structure, and having both surfaces in the thickness direction thereof being skin layers, the value obtained by dividing the apparent density of the aforementioned skin layers by the apparent density of the three-dimensional network structure being 1.25 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to three-dimensional mesh structures. Background Technology

[0002] In the past, three-dimensional mesh structures have been widely used as cushioning materials for furniture, bedding such as beds, and seats in vehicles such as trams, cars, and motorcycles, due to their excellent breathability and recyclability.

[0003] For example, Patent Document 1 discloses a mesh structure that is lightweight, has excellent hardness, and is highly durable by foaming continuous lines that constitute a three-dimensional random ring joint structure and by covering the outside of the foamed layer with a non-foamed layer.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Publication No. 2014 / 192790 Summary of the Invention

[0007] The problem the invention aims to solve

[0008] However, in the manufacturing method of Patent Document 1, it is difficult to control the foaming property in the extrusion molding process, resulting in problems with production stability. On the other hand, the three-dimensional mesh structure obtained by the conventional manufacturing method described in the comparative example below cannot fully achieve lightweighting.

[0009] The present invention was made in view of the above circumstances, and its purpose is to obtain a three-dimensional mesh structure that is relatively simple to manufacture and, although it has excellent cushioning performance, is lighter than the previous one.

[0010] Solution for solving the problem

[0011] The three-dimensional mesh structure of the present invention is described below.

[0012] [1] A three-dimensional mesh structure, characterized in that it is composed of continuous lines and has a three-dimensional random ring joint structure, wherein the continuous lines are composed of a thermoplastic resin composition, and both surfaces of the three-dimensional mesh structure in the thickness direction are skin layers, wherein the apparent density of the skin layer divided by the apparent density of the three-dimensional mesh structure is less than 1.25.

[0013] [2] According to the three-dimensional mesh structure described in [1] above, the three-dimensional mesh structure has an inner layer sandwiched between two epidermal layers, and the average fiber diameter of the lines constituting the epidermal layer and the inner layer is 0.1 mm to 3.0 mm.

[0014] [3] According to the three-dimensional mesh structure described in [1] or [2] above, wherein the apparent density of the three-dimensional mesh structure is 0.01 g / cm³. 3 ~0.20g / cm 3 The apparent density of the epidermis is 0.01 g / cm³. 3 ~0.20g / cm 3 .

[0015] [4] The thickness of the three-dimensional mesh structure according to any one of [1] to [3] above is 10 to 300 mm.

[0016] The effects of the invention

[0017] The method for manufacturing the three-dimensional mesh structure of the present invention is relatively simple, and it is possible to obtain a three-dimensional mesh structure that is lighter than before due to a reduction in the apparent density of the skin layer, yet possesses excellent cushioning performance. By using the three-dimensional mesh structure of the present invention, weight reduction can be achieved in various applications, resulting in a reduction in environmental impact. In addition to the reduction in environmental impact due to weight reduction, when used as bedding, the bedding can be made lighter, thus reducing the load during transportation; when used as seats in vehicles such as railways, automobiles, and two-wheeled vehicles, the vehicle body weight can be reduced, thus reducing the energy required for vehicle operation. Detailed Implementation

[0018] The three-dimensional mesh structure of the present invention is composed of continuous lines and has a three-dimensional random ring joint structure, wherein the continuous lines are composed of a thermoplastic resin composition. Specifically, the continuous lines composed of the thermoplastic resin composition are bent to form random rings, and the rings are brought into contact with each other in a molten state to form a three-dimensional random ring joint structure.

[0019] In this invention, both surfaces of the three-dimensional mesh structure in the thickness direction are skin layers, and the layer sandwiched between the two skin layers disposed on the two surfaces of the three-dimensional mesh structure is called the inner layer. Hereinafter, the thermoplastic resin composition constituting the three-dimensional mesh structure of this invention, the characteristics of the three-dimensional mesh structure of this invention, and the manufacturing method of the three-dimensional mesh structure of this invention will be described in sequence.

[0020] <Thermoplastic Resin Composition>

[0021] Thermoplastic resins are not particularly limited, but thermoplastic elastomers or biodegradable thermoplastic resins are preferred. From a cushioning point of view, thermoplastic resins are preferably thermoplastic elastomers. On the other hand, in applications where excellent environmental adaptability is important, thermoplastic resins that are biodegradable are preferred. Examples of thermoplastic elastomers include polyester-based thermoplastic elastomers, polyolefin-based thermoplastic elastomers, styrene-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, and thermoplastic ethylene-vinyl acetate copolymer elastomers.

[0022] Examples of polyester-based thermoplastic elastomers include polyether ester block copolymers with thermoplastic polyester as the hard segment and polyalkylene glycol as the soft segment, or polyester ester block copolymers with aliphatic polyester as the soft segment.

[0023] Examples of polyether ester block copolymers include block copolymers composed of dicarboxylic acids, diol components, and polyalkylene glycols. The dicarboxylic acid is not particularly limited, but is preferably selected from at least one of aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, naphthal-2,6-dicarboxylic acid, naphthal-2,7-dicarboxylic acid, and diphenyl-4,4'-dicarboxylic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and dimer acids; or their ester-forming derivatives. The diol component is not particularly limited, but is preferably selected from at least one of aliphatic diols such as 1,4-butanediol, ethylene glycol, trimethylenediol, tetramethylenediol, pentamethylenediol, and hexamethylenediol; alicyclic diols such as 1,1-cyclohexanediethanol and 1,4-cyclohexanediethanol; or their ester-forming derivatives. The polyalkylene glycol is not particularly limited, but is preferably at least one of polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and a glycol formed from an ethylene oxide-propylene oxide copolymer. Furthermore, the number average molecular weight of the polyalkylene glycol is preferably 300 to 5000, more preferably 500 to 3000.

[0024] Examples of polyester block copolymers include block copolymers composed of dicarboxylic acids, glycol components, and polyester glycols. Examples of dicarboxylic acids and glycol components used to form polyester block copolymers include the aforementioned dicarboxylic acids and glycol components. Examples of polyester glycols include polylactones with a number average molecular weight of about 300 to 5000.

[0025] Considering thermal adhesion, hydrolysis resistance, elasticity, and heat resistance, for each unit constituting the polyether ester block copolymer, terephthalic acid and / or naphthalene-2,6-dicarboxylic acid are particularly preferred, as are 1,4-butanediol and polytetramethylene glycol. Similarly, for each unit constituting the polyester ester copolymer, terephthalic acid and / or naphthalene-2,6-dicarboxylic acid are particularly preferred, as are 1,4-butanediol and polylactone. It should be noted that polyether ester block copolymers incorporating polysiloxane-based soft segments can also be used.

[0026] The soft segment content of the polyester thermoplastic elastomer is preferably 15-80% by mass, more preferably 25-70% by mass, even more preferably 30-60% by mass, and particularly preferably 35-50% by mass. When the soft segment content is 15% by mass or more, compression durability can be easily improved. In addition, when the soft segment content is 80% by mass or less, hardness, heat resistance, and resistance to permanent deformation are easily maintained.

[0027] As a polyolefin-based thermoplastic elastomer, it is preferably an ethylene-α-olefin copolymer formed by copolymerizing ethylene with α-olefins having 3 or more carbon atoms, more preferably an ethylene-α-olefin copolymer formed by copolymerizing ethylene with α-olefins having 3 to 10 carbon atoms, and even more preferably an ethylene-α-olefin copolymer formed by copolymerizing ethylene with α-olefins having 3 to 8 carbon atoms.

[0028] Examples of α-olefins having 3 or more carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetracene, 1-tetradecene, 1-pentadecadecene, 1-hexadecene, 1-heptadecene, 1-heptadecene, 1-octadecene, 1-nonadecadecene, and 1-eicosene, with 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetracene, 1-tetradecene, 1-pentadecadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecadecene, and 1-eicosene being preferred. α-olefins having 3 or more carbon atoms can be used alone or in combination.

[0029] Ethylene-α-olefin copolymers can be random copolymers or multi-block copolymers. Random copolymers can be obtained by copolymerizing ethylene and α-olefins using metallocene compounds as catalysts, while multi-block copolymers can be obtained by copolymerizing ethylene and α-olefins using chain shuttle reaction catalysts. Depending on the requirements, polymers polymerized by the above methods, such as hydrogenated polybutadiene and hydrogenated polyisoprene, can be blended.

[0030] In the ethylene-α-olefin copolymer, the ratio of ethylene to α-olefins with 3 or more carbon atoms is preferably 70% by mass or more and 95% by mass or less for ethylene, and 5% by mass or more and 30% by mass or less for α-olefins with 3 or more carbon atoms. Generally, it is known that polymers achieve elastomeric properties due to the presence of hard and soft segments within the polymer chain. In the polyolefin-based thermoplastic elastomer used in this invention, ethylene is considered to act as a hard segment, and α-olefins with 3 or more carbon atoms are considered to act as soft segments. Therefore, when the ethylene ratio is less than 70% by mass, there are fewer hard segments, thus reducing the elastic recovery performance of the rubber. The ethylene ratio is more preferably 75% by mass or more, and even more preferably 80% by mass or more. On the other hand, when the ethylene ratio exceeds 95% by mass, there are fewer soft segments, making it difficult to achieve elastomeric properties, and the cushioning performance may deteriorate. The ethylene ratio is more preferably 93% by mass or less, and even more preferably 90% by mass or less.

[0031] As a polyurethane-based thermoplastic elastomer, a representative example is a polyurethane elastomer obtained by chain extension of a prepolymer with a polyamine, primarily composed of a diamine, in the presence or absence of a common solvent (dimethylformamide, dimethylacetamide, etc.). The prepolymer is a prepolymer with isocyanate groups at both ends, obtained by reacting a polyether and / or polyester with a number-average molecular weight of 1000-6000 and terminal hydroxyl groups with a polyisocyanate, primarily composed of an organic diisocyanate. Preferably, the polyester and / or polyether are polybutylene adipate copolyesters, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, or polyalkylene glycols formed from ethylene oxide-propylene oxide copolymers, etc., with a number-average molecular weight of about 1000-6000, preferably 1300-5000. As polyisocyanates, conventionally known polyisocyanates can be used, including isocyanates based on diphenylmethane 4,4'-diisocyanate, with trace amounts of conventionally known triisocyanates added as needed. As polyamines, known diamines such as ethylenediamine and 1,2-propanediamine can be used as the main components, with trace amounts of triamines and tetraamines added as needed. Polyurethane-based thermoplastic elastomers can use two or more types alone or in combination.

[0032] From the viewpoint of excellent compression durability, the soft segment content of the polyurethane thermoplastic elastomer is preferably 15% by mass or more, more preferably 25% by mass or more, further preferably 30% by mass or more, and most preferably 40% by mass or more. From the viewpoint of ensuring excellent hardness and heat resistance and resistance to permanent deformation, it is preferably 80% by mass or less, and more preferably 70% by mass or less.

[0033] Examples of polyamide-based elastomers include substances copolymerized from polyamides as hard segments and polyols as soft segments. Examples of polyamides as hard segments include at least one type of polyamide oligomer obtained from the reaction of lactam compounds with dicarboxylic acids, or diamines with dicarboxylic acids. Examples of polyols as soft segments include at least one type of polyether polyols, polyester polyols, and polycarbonate polyols.

[0034] Examples of lactam compounds include at least one aliphatic lactams with 5 to 20 carbon atoms, such as γ-butyrolactam, ε-caprolactam, ω-heptylactam, ω-undecaprolactam, and ω-laurolactam.

[0035] Examples of dicarboxylic acids include aliphatic dicarboxylic acids with 2 to 20 carbon atoms, such as oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, and dodecanoic acid; at least one of alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, and phthalic acid.

[0036] As diamines, at least one of the following can be listed: ethylenediamine, trimethylenediamine, tetramethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 3-methylpentamethylenediamine, etc., aliphatic diamines, or aromatic diamines such as m-phenylenediamine. Regarding polyols, as polyether polyols, at least one of the following can be listed: polyethylene glycol, polypropylene glycol, polytetramethylenediamine, and diols formed from ethylene oxide-propylene oxide copolymers, etc., with a number average molecular weight of about 300 to 5000. Furthermore, as polycarbonate diols, which are reactants of low molecular weight diols and carbonate compounds, polycarbonate diols with a number average molecular weight of about 300 to 5000 can be listed. Examples of low-molecular-weight diols include at least one aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol, as well as alicyclic diols such as cyclohexanediol and cyclohexanediol. Examples of carbonate compounds include at least one dialkyl carbonate, alkylene carbonate, and diaryl carbonate. Furthermore, examples of polyester polyols include at least one polyester diol such as polylactone with a number average molecular weight of approximately 300 to 5000.

[0037] From the viewpoint of excellent compression durability, the soft segment content of the polyamide thermoplastic elastomer is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, and most preferably 20% by mass or more. From the viewpoint of ensuring excellent hardness and heat resistance and resistance to permanent deformation, it is preferably 80% by mass or less, and more preferably 70% by mass or less.

[0038] The content of the constituent units derived from vinyl acetate monomer in the thermoplastic ethylene vinyl acetate copolymer elastomer is preferably 1 to 35% by mass, more preferably 2 to 30% by mass, and even more preferably 3 to 26% by mass. By keeping the content of the structural units derived from vinyl acetate monomer within the above range, it is easy to balance the elasticity and heat resistance of the rubber.

[0039] Thermoplastic ethylene-vinyl acetate copolymer elastomers can also copolymerize α-olefins with more than 3 carbon atoms. Examples of α-olefins having 3 or more carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetracene, 1-tetradecene, 1-pentadecadecene, 1-hexadecene, 1-heptadecene, 1-heptadecene, 1-octadecene, 1-nonadecadecene, and 1-eicosene, with 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetracene, 1-tetradecene, 1-pentadecadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecadecene, and 1-eicosene being preferred. α-olefins having 3 or more carbon atoms can be used alone or in combination.

[0040] As a biodegradable thermoplastic resin, there are no particular limitations, but examples include polybutylene succinate, poly(butylene succinate / butylene adipate), poly(butylene adipate / butylene terephthalate), polylactic acid, (polylactic acid / polybutylene succinate-based) block copolymers, polycaprolactone, poly(caprolactone / butylene succinate), poly(butylene succinate / butylene carbonate), poly(ethylene terephthalate / ethylene succinate), poly(butylene adipate / butylene terephthalate), polyethylene succinate, polyvinyl alcohol, and polyglycolic acid. From a buffering perspective, poly(butylene adipate / butylene terephthalate) is preferred.

[0041] The thermoplastic resin composition constituting a continuous line can utilize two or more different thermoplastic resins, depending on the intended purpose. When a mixture of two or more different thermoplastic resins is used as the thermoplastic resin composition constituting the continuous line, the total amount of polyester-based thermoplastic elastomers, polyolefin-based thermoplastic elastomers, styrene-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, and thermoplastic ethylene-vinyl acetate copolymer elastomers is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. In particular, the total amount of polyester-based thermoplastic elastomers and polyolefin-based thermoplastic elastomers is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.

[0042] The thermoplastic resin composition constituting a continuous line can be formulated with various additives according to the purpose. Examples of additives include, for instance, plasticizers such as phthalate-based, trimelliticate-based, fatty acid-based, epoxy-based, adipate-based, and polyester-based plasticizers; known hindered phenolic, sulfur-based, phosphorus-based, and amine-based antioxidants; hindered amine-based, triazole-based, benzophenone-based, benzoate-based, nickel-based, and salicylic acid-based light stabilizers; antistatic agents; molecular weight regulators such as peroxides; compounds with reactive groups such as epoxy compounds, isocyanate compounds, and carbodiimide compounds; metal passivators; neutralizers; acid stabilizers; antibacterial agents; fluorescent whitening agents; fillers; flame retardants; flame retardant additives; nucleating agents of organic and inorganic systems; and pigments of organic and inorganic systems. These can be used alone or in combination of two or more. In 100% by mass of the thermoplastic resin composition, the total amount of various additives is preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less.

[0043] <Characteristics of Three-Dimensional Mesh Structures>

[0044] The apparent density of the three-dimensional mesh structure of the present invention is preferably 0.01 g / cm³. 3 ~0.20g / cm 3 More preferably, it is 0.02 g / cm³. 3 ~0.10g / cm 3 Further preferably, it is 0.02 g / cm³. 3 ~0.07g / cm 3 The apparent density of the epidermis is preferably 0.01 g / cm³. 3 ~0.20g / cm 3 More preferably, it is 0.02 g / cm³. 3 ~0.10g / cm 3 Further optimization yielded an apparent density of 0.02 g / cm³. 3 ~0.07g / cm 3 .

[0045] The density ratio of the skin layer, obtained by dividing the apparent density of the skin layer by the apparent density of the three-dimensional network structure, is 1.25 or less, preferably 0.7 to 1.25, more preferably 0.8 to 1.2, and even more preferably 0.85 to 1.15. The inventors have discovered that the skin layer contributes little to compressive hardness. By using the manufacturing method described later to set the density ratio of the skin layer to 1.25 or less, a lightweight three-dimensional network structure can be obtained without reducing compressive hardness. It should be noted that, unless otherwise specified, "apparent density of the skin layer" refers to the average apparent density of the two surfaces.

[0046] From the perspective of balancing lightweight and excellent compressive strength, it is preferable to make the apparent density of the epidermis layer close to the apparent density of the overall three-dimensional network structure. Therefore, the apparent density A (g / cm³) of the three-dimensional network structure is... 3 ) and the apparent density B (g / cm³) of the epidermis 3 The relationship preferably satisfies A+0.012≥B≥A-0.004, and more preferably satisfies A+0.010≥B≥A-0.002.

[0047] Furthermore, the apparent density of the epidermal layer on both surfaces is preferably the same, and the difference in apparent density between the epidermal layers on the two surfaces is preferably 0.005 g / cm³. 3 The preferred value is 0.003 g / cm³. 3 the following.

[0048] The average fiber diameter of the lines (fibers) constituting the epidermal layer is preferably 0.1 mm to 3.0 mm, more preferably 0.2 mm to 3.0 mm, and even more preferably 0.3 mm to 1.0 mm. The average fiber diameter of the lines (fibers) constituting the inner layer is preferably 0.1 mm to 3.0 mm, more preferably 0.2 mm to 3.0 mm, and even more preferably 0.3 mm to 1.0 mm.

[0049] From the viewpoint of balancing lightweight and excellent compressive stiffness, the thickness of the three-dimensional mesh structure of the present invention is preferably 10~300mm, more preferably 15~200mm, even more preferably 20~100mm, and particularly preferably 30~60mm.

[0050] Continuous lines can also be composite lines such as core-sheath type, side-by-side type, or eccentric core-sheath type. Composite lines can also be composed of a thermoplastic elastomer and a thermoplastic resin other than a thermoplastic elastomer. The cross-sectional shape of the continuous line can be any type, including hollow and solid cross-sections, but a hollow cross-section is preferred from a lightweight perspective. The lower limit of the hollow ratio of the continuous line is preferably 5% or more, more preferably 10% or more, and particularly preferably 15% or more. On the other hand, the upper limit of the hollow ratio of the continuous line is not particularly limited, for example, it is 60% or less. The hollow ratio of the continuous line can be measured by the method described in the examples below.

[0051] The cross-sectional shape of the continuous lines constituting the three-dimensional mesh structure of the present invention is not particularly limited; it can be a roughly circular cross-section or an irregular cross-section that is not roughly circular. By setting it to an irregular cross-section, it is sometimes possible to impart compressibility and tactile properties.

[0052] The three-dimensional mesh structure of the present invention can also be configured as a multi-layer structure without compromising the purpose of the present invention. Examples of multi-layer structures include structures with outer and inner layers composed of continuous lines of different fineness; structures with outer and inner layers composed of different raw materials; structures with outer and inner layers composed of structures with different apparent densities; and structures formed by stacking long-fiber nonwoven fabrics, short-fiber nonwoven fabrics, etc. Examples of multi-layering methods include: stacking mesh structures on top of each other and fixing them using side materials; melting and solidifying them by heating; bonding them using adhesives; and restraining them using sewing, tape, etc.

[0053] The shape of the three-dimensional mesh structure of the present invention is not particularly limited. Examples include plate-shaped, triangular prism, quadrangular prism and other polygonal shapes, cylinder, sphere, and combinations thereof. When forming the three-dimensional mesh structure, it can also be formed by cutting, hot pressing, non-woven fabric processing, etc.

[0054] The appropriate hardness of a three-dimensional mesh structure varies depending on its application, so it is impossible to specify a single appropriate hardness value. However, if the hardness is too high, the cushioning effect will be compromised; if the hardness is too low, it will bottom out and fail to function as a cushioning material. Therefore, it is necessary to adjust the hardness to an appropriate level according to the application.

[0055] <Manufacturing Method of Three-Dimensional Mesh Structures>

[0056] Next, the method for manufacturing the three-dimensional mesh structure of the present invention will be described, but the following method is only one example and is not limited to the following method.

[0057] First, a thermoplastic resin composition is dispensed from multiple rows of nozzles with multiple orifices, and discharged downwards from the nozzles at a spinning temperature where the resin's melting point is above +10°C and below +120°C. Next, a continuous thread formed from the thermoplastic resin composition molten at the aforementioned spinning temperature is dropped onto a pair of adjustable-interval traction conveyors mounted on a cooling medium. The molten continuous thread is clamped into the traction conveyors, held, and bent, causing the continuous thread to come into contact with and fuse together, forming a three-dimensional random ring-joined structure. Then, the mesh structure with the three-dimensional random ring-joined structure is introduced into the cooling medium and allowed to solidify, thereby obtaining the three-dimensional mesh structure of the present invention. It should be noted that the spacing between the orifices needs to be adjusted beforehand to form the aforementioned rings.

[0058] The thickness of the three-dimensional mesh structure is determined by the interval between a pair of traction conveyors. However, in the past, in order to enable the traction conveyors to transport materials well, the range of resin discharge was usually wider than the interval between the traction conveyors. The lines discharged to the outer edge of the traction conveyors converged on the surface of the three-dimensional mesh structure to form a skin layer.

[0059] The apparent density of the skin layer is higher than that of the overall three-dimensional mesh structure. However, in this invention, by making the density ratio of the skin layer less than 1.25, which is lower than before, the apparent density of the skin layer is made close to that of the overall three-dimensional mesh structure, thus obtaining a three-dimensional mesh structure that exhibits high resilience. Methods for reducing the density ratio of the skin layer include: controlling the amount of resin discharged from the nozzle by independently setting a gear pump for each discharge range in the thickness direction; changing the density of the nozzles (nozzles that discharge resin for forming the skin layer) existing in the range corresponding to the skin layer; adjusting the resin discharge range in the thickness direction (the range of resin discharged from the nozzle) relative to the interval of a pair of traction conveyors; and generating water flow or bubbles near the center of a pair of traction conveyors in a manner opposing the conveying direction. These methods reduce the apparent density of the skin layer, which contributes little to compressive strength, and enable the obtaining of a lightweight three-dimensional mesh structure without reducing compressive strength. Preferably, the resin discharge rate from the nozzles is controlled by independently setting a gear pump or similar method for each discharge range in the thickness direction. The ratio obtained by increasing the resin discharge rate (single-hole discharge rate) from each nozzle discharging resin for forming the inner layer (single-hole discharge rate) divided by the resin discharge rate (single-hole discharge rate) from each nozzle discharging resin for forming the skin layer (single-hole discharge rate) (hereinafter referred to as the single-hole discharge rate ratio) is (preferably 1.2 to 3.0, more preferably 1.3 to 2.5). However, even if the single-hole discharge rate ratio is around 1.0, the density ratio of the skin layer can be reduced to 1.25 or less by changing manufacturing conditions other than the single-hole discharge rate ratio. On the other hand, if the single-hole discharge rate ratio is too large, the average fiber diameter of the skin layer may become extremely small. However, this can be avoided by reducing the spinning temperature only in the skin layer area, locally changing the distance to the water tank by setting a height difference on the nozzle surface, or creating differences in the outer diameter of the nozzles. It should be noted that the above-described method for controlling the single-hole discharge rate ratio is an example and is not limited to the method described above. Furthermore, when the average fiber diameter of the epidermis is extremely small compared to the average fiber diameter of the inner layer, the cushioning effect is sometimes reduced. Therefore, as mentioned above, it is preferable that the difference between the average fiber diameters of the epidermis and the inner layer is small.

[0060] It should be noted that the conveying of three-dimensional mesh structures with a low density ratio of the skin layer can sometimes become unstable. However, in the case of unstable conveying, the holding force of the traction conveyor can be improved by coating the surface of the traction conveyor to increase the friction between the traction conveyor and the three-dimensional mesh structure, or by setting small protrusions near the surface of the traction conveyor, thereby enabling stable conveying.

[0061] Cooling water is preferably used to cool the thermoplastic resin after melt molding.

[0062] To further improve the heat resistance and anti-sagging properties of the three-dimensional network structure, annealing is preferably performed after the aforementioned cooling. Annealing can be performed using a commercially available hot air drying oven or in a hot water bath. It is believed that annealing rearranges the hard segments, forming pseudo-crystalline crosslinking points, thus improving heat resistance and resistance to permanent deformation. The annealing temperature is preferably 80°C or higher, more preferably 100°C or higher.

[0063] This application claims the benefit of priority based on Japanese Patent Application No. 2024-052441, filed on March 27, 2024. The entire contents of the description of Japanese Patent Application No. 2024-052441, filed on March 27, 2024, are incorporated herein by reference.

[0064] Example

[0065] The present invention will be described in more detail below with examples. It should be noted that the present invention is not limited to the examples described below. In addition, modifications can be made to implement the invention within the scope of the foregoing and following spirit, and all such modifications are included within the technical scope of the present invention.

[0066] The evaluation methods used in the examples and comparative examples are described below.

[0067] (1) Thickness, apparent density

[0068] The three-dimensional mesh structure was cut into 30cm × 30cm pieces along both longitudinal and transverse directions, and the resulting samples were placed under no load for 24 hours. Then, using a test piece thickness gauge (FD-80N type, Polymer Instruments Co., Ltd.), the height at the center point was measured, and the average value was taken as the thickness of the three-dimensional mesh structure. Next, the sample was placed on an electronic balance, and the mass of the sample was measured. The sample height was multiplied by the area (900cm²) of the cross-section. 2 The volume of the sample is then determined, and the apparent density is calculated by dividing the mass of the sample by the volume. This process is repeated four times to obtain the average thickness and apparent density of the three-dimensional network structure.

[0069] (2) Density ratio of the epidermis

[0070] The three-dimensional mesh structure was cut into 5cm × 5cm pieces along the longitudinal and transverse directions. The thickness and apparent density (overall apparent density) of the obtained samples were measured using the same method as described in (1). Next, the samples were cut at a distance of 0.5cm along the thickness direction from both surfaces. The apparent density (g / cm³) of the epidermis was calculated by dividing the total mass (g) of the two cut samples by the volume (5cm × 5cm × 0.5cm × 2). 3Finally, the apparent density of the epidermis is divided by the overall apparent density to obtain the density ratio of the epidermis. This measurement is performed three times to determine the density ratio of the epidermis (n=3).

[0071] (3) Average fiber diameter

[0072] The three-dimensional mesh structure was cut into 10cm × 10cm pieces in both the longitudinal and transverse directions. Next, 10 fibers from the outermost layer of the mesh structure in the thickness direction were collected, representing the epidermal layer. These fibers were located at points where no fibers existed in the thickness direction. Finally, the diameter of the fibers was measured by focusing on the collected continuous lines using an optical microscope. The average fiber diameter at these 10 locations (n ​​= 10) was calculated as the average fiber diameter in the epidermal layer.

[0073] Regarding the average fiber diameter of the fibers in the inner layer, fibers were also collected from a range of 30% of the thickness (35-65% of the thickness from one surface) with the center of the thickness direction of the three-dimensional mesh structure as the reference. Otherwise, the average fiber diameter was calculated using the same method as that of the fibers in the epidermis.

[0074] (4) Hollow rate

[0075] The sample was cut into 10cm × 10cm pieces. Next, for the epidermal layer, 10 fibers located on the outermost surface of the three-dimensional network structure in the thickness direction were collected—that is, fibers located in areas where no fibers exist on the outer side of the thickness direction. The collected fibers were cut into circular slices and placed vertically on a coverslip along the fiber axis. The cross-section of the fibers along the direction of the slices was observed using an optical microscope. The outer circumferential area (a) and hollow area (b) of the fibers were calculated, and the hollowness ratio was calculated using the following formula. The average hollowness ratio of the 10 fibers was taken as the hollowness ratio of the fibers in the epidermal layer.

[0076] Hollow rate = 100 × (b) / (a) (unit %)

[0077] Regarding the hollowness of the fibers in the inner layer, in addition to collecting fibers from the center of the thickness direction of the three-dimensional mesh structure within a range of 30% of the thickness (from one surface within a range of 35 to 65% of the thickness direction), the hollowness of the fibers in the epidermis is also calculated using the same method.

[0078] (5) Compression hardness

[0079] The three-dimensional mesh structure was cut into 30cm × 30cm pieces, and the resulting samples were placed unloaded at 20℃ ± 2℃ for 24 hours. Then, measurements were performed at 20℃ ± 2℃ using an ORIENTEC Tensilon according to JIS L 4500. Specifically, a pressure plate with a diameter (φ) of 200mm and a thickness of 3mm was placed at the center of the sample, and compression of the center of the sample was initiated at a speed of 10mm / min. The thickness at which the load reached 5N was measured and taken as the initial thickness. Using the position of the pressure plate at this point as the zero point, a pre-compression was performed once along the thickness direction at a speed of 100mm / min until 75% (25% of the initial thickness). The pressure plate was then returned to the zero point at the same speed. Immediately afterwards, a 25% compression was performed along the thickness direction at a speed of 100mm / min (compressed to 75% of the initial thickness), and the load at this point was measured. This load was taken as the hardness at 25% compression (N / φ200mm). Perform the above operation three times and calculate the average hardness at 25% compression (n=3).

[0080] Next, a 50% compression was performed along the thickness direction at a speed of 100 mm / min (compressed to 50% of the initial thickness), and the load at this point was measured. This load was taken as the hardness at 50% compression (N / φ200mm). The above operation was performed three times, and the average hardness at 50% compression was calculated (n=3).

[0081] As the thermoplastic resin compositions used in the examples and comparative examples, the following resin A was prepared as a polyester-based thermoplastic elastomer, the following resin B was prepared as a polyolefin-based thermoplastic elastomer, and the following resin C was prepared as a biodegradable resin.

[0082] <Resin A>

[0083] Dimethyl terephthalate (DMT) and 1,4-butanediol (1,4-BD) with a small amount of catalyst were introduced and subjected to transesterification using conventional methods. Then, polytetramethylene glycol (PTMG) with a number average molecular weight of 1000 was added, and polycondensation was carried out under reduced pressure and increased temperature to generate a polyether ester block copolymer elastomer. Next, 1% antioxidant was added, and the mixture was compounded, granulated, and vacuum dried at 50°C for 48 hours to obtain a polyester-based thermoplastic elastomer (resin A). Resin A has a soft segment content of 40% by mass and a melting point of 198°C.

[0084] <Resin B>

[0085] Using metallocene compounds as catalysts, hexane, 1-hexene, and ethylene were polymerized via a known method to prepare an ethylene-α-olefin copolymer. Then, 1% antioxidant was added, and the mixture was compounded and granulated to obtain a polyolefin-based thermoplastic elastomer (Resin B). Resin B is a random copolymer with 6.2% by mass of 1-hexene-derived structural units and a density of 0.912 g / cm³. 3 It has a melting point of 110℃ and an intrinsic viscosity of 0.99 dL / g.

[0086] <Resin C>

[0087] In a reactor equipped with a stirrer, thermometer, and distillation cooler, 1.5 mol of 1,4-butanediol, 0.40 mol of adipic acid, and 0.60 mol of dimethyl terephthalate were mixed. Then, 300 ppm of tetrabutyl titanate (Aldrich) as a titanium-based catalyst was added to the resulting mixture. The transesterification and esterification reactions were then carried out at atmospheric pressure and 220°C for 2 hours to prepare a prepolymer. The resulting prepolymer was heated to 240°C and subjected to condensation polymerization at 0.1 mmHg for 2 hours. After cooling, the prepolymer was granulated using a pellet cutter to obtain poly(butylene adipate / butylene terephthalate) resin granules (resin C).

[0088] <Example 1>

[0089] Resin A is melted and discharged below the nozzle surface equipped with a discharge nozzle. The nozzle is arranged in eight rows along the thickness direction on its effective surface, which has a width length of 97 cm and a thickness length of 59.7 mm. The nozzles are configured as hollow orifices with a triple-bridge shape, having an outer diameter of 5.8 mm and an inner diameter of 5.3 mm. In rows 2-7, the orifices are arranged in an alternating pattern with a width spacing of 9.0 mm and a thickness spacing of 7.8 mm. In rows 1 and 8, the orifices are arranged with a width spacing of 12 mm and a thickness spacing of 11.5 mm. The resin discharged from the nozzles in rows 1 and 8 in the thickness direction forms the outer skin layer, and the resin discharged from the nozzles in rows 2-7 in the thickness direction forms the inner layer.

[0090] Molten resin A is discharged below the nozzle surface at a spinning temperature (melt temperature) of 240°C, an average single-hole discharge rate of 4.0 g / min, and a ratio (hereinafter referred to as the single-hole discharge rate ratio) of 2.0 obtained by dividing the single-hole discharge rate of the nozzles in rows 2 to 7 forming the inner layer by the single-hole discharge rate of the nozzles in rows 1 and 8 forming the skin layer. Below the nozzle surface, a water tank is positioned such that the cooling water surface is 35 cm below the nozzle surface of the discharge nozzle. A pair of traction conveyors are arranged within the water tank, with a portion protruding above the water surface. The traction conveyors have a 150 cm wide stainless steel annular mesh, which is arranged parallel to the width direction of the nozzle surface, and the opening width of the annular mesh is set to 43 mm.

[0091] On a traction conveyor on the water surface, the molten resin is discharged in lines, causing the continuous lines to fall and bend to form loops, fusing the contact parts and forming a three-dimensional mesh structure. The molten three-dimensional mesh structure is clamped on both sides by the traction conveyor and introduced into cooling water at a traction speed of 2.70 m / min to solidify. Solidification flattens both sides in the thickness direction. Next, it is cut to a specified size and heat-treated with 110°C hot air for 15 minutes to obtain the three-dimensional mesh structure.

[0092] In the obtained three-dimensional network structure, the average fiber diameter of the epidermal layer is 0.80 mm, and the average fiber diameter of the inner layer is 0.85 mm. Furthermore, the fibers in the epidermal layer have a cylindrical cross-section with a hollow section ratio of 31%, while the fibers in the inner layer have a cylindrical cross-section with a hollow section ratio of 35%. The apparent density of the obtained three-dimensional network structure is 0.033 g / cm³. 3 The surface layer density ratio is 1.00, and the thickness is 41 mm. The resulting three-dimensional mesh structure has a hardness of 140.1 N at 25% compression and 242.0 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 1.

[0093] <Example 2>

[0094] The single-hole discharge ratio was set to 1.4, the water tank was configured such that the cooling water surface was 34 cm below the nozzle surface, and the traction speed was set to 2.55 m / min. Otherwise, it was carried out in the same manner as in Example 1 to obtain a three-dimensional mesh structure.

[0095] In the obtained three-dimensional network structure, the average fiber diameter of the epidermal layer is 0.78 mm, and the average fiber diameter of the inner layer is 0.85 mm. Furthermore, the fibers in the epidermal layer have a cylindrical cross-section with a hollow section ratio of 32%, while the fibers in the inner layer have a cylindrical cross-section with a hollow section ratio of 36%. The apparent density of the obtained three-dimensional network structure is 0.035 g / cm³. 3 The surface layer density ratio is 1.22, and the thickness is 40 mm. The resulting three-dimensional mesh structure has a hardness of 138.1 N at 25% compression and 239.5 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 1.

[0096] <Example 3>

[0097] The single-hole discharge ratio was set to 2.3, the water tank was configured such that the cooling water surface was 32 cm below the nozzle surface, and the traction speed was set to 2.62 m / min. Otherwise, it was carried out in the same manner as in Example 1 to obtain a three-dimensional mesh structure.

[0098] In the obtained three-dimensional network structure, the average fiber diameter of the epidermal layer is 0.75 mm, and the average fiber diameter of the inner layer is 0.89 mm. Furthermore, the fibers in the epidermal layer have a cylindrical cross-section with a hollow section ratio of 29%, while the fibers in the inner layer have a cylindrical cross-section with a hollow section ratio of 35%. The apparent density of the obtained three-dimensional network structure is 0.034 g / cm³. 3 The surface layer density ratio is 1.10, and the thickness is 40 mm. The resulting three-dimensional mesh structure has a hardness of 137.9 N at 25% compression and 245.3 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 1.

[0099] <Comparative Example 1>

[0100] Eight rows of nozzles are arranged along the thickness direction on the effective surface of a nozzle with a width length of 97 cm and a thickness length of 54.6 mm. The nozzles are configured as hollow orifices with a triple-bridge shape, having an outer diameter of 5.0 mm and an inner diameter of 4.4 mm. In rows 1-8, the orifices are arranged in an alternating pattern with a width spacing of 9.0 mm and a thickness spacing of 7.8 mm. The single-orifice discharge ratio is set to 1.0. A water tank is positioned with the cooling water surface 32 cm below the nozzle surface. The traction speed is set to 2.34 m / min. Otherwise, the process is the same as in Example 1, resulting in a three-dimensional mesh structure. It should be noted that Comparative Example 1 does not distinguish between nozzles for forming the outer skin layer and nozzles for forming the inner layer; for convenience, the single-orifice discharge ratio is recorded as 1.0.

[0101] In the obtained three-dimensional network structure, the average fiber diameter of the epidermal layer is 0.86 mm, and the average fiber diameter of the inner layer is 0.84 mm. Furthermore, the fibers in the epidermal layer have a cylindrical cross-section with a hollow section ratio of 34%, while the fibers in the inner layer have a cylindrical cross-section with a hollow section ratio of 33%. The apparent density of the obtained three-dimensional network structure is 0.038 g / cm³. 3 The surface layer density ratio is 1.38, and the thickness is 42 mm. The resulting three-dimensional mesh structure has a hardness of 140.2 N at 25% compression and 241.0 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 1.

[0102] <Example 4>

[0103] Resin A is melted and discharged below the nozzle surface equipped with a discharge nozzle. The nozzle has nine rows arranged along its thickness direction on its effective surface, which is 97 cm long in the width direction and 67 mm long in the thickness direction. The nozzles are hollow orifices with a triple-bridge shape, having an outer diameter of 5.8 mm and an inner diameter of 5.3 mm. In rows 2-8, the orifices are arranged in an alternating pattern with a width-direction spacing of 9.0 mm and a thickness-direction spacing of 7.8 mm. In rows 1 and 9, the orifices are arranged with a width-direction spacing of 12 mm and a thickness-direction spacing of 11.5 mm. The resin discharged from the nozzles in rows 1 and 9 in the thickness direction forms the outer skin layer, and the resin discharged from the nozzles in rows 2-8 in the thickness direction forms the inner layer.

[0104] Molten resin A is discharged below the nozzle surface at a spinning temperature (melt temperature) of 240℃, an average single-hole discharge rate of 3.3 g / min, and a single-hole discharge rate ratio of 2.0. Below the nozzle surface, a water tank is positioned with the cooling water surface 30 cm below the nozzle surface of the discharge nozzle. A pair of traction conveyors are arranged within the water tank, with a portion protruding above the water surface. The traction conveyors have a 150 cm wide stainless steel annular mesh, arranged parallel to the width direction of the nozzle surface and the traction conveyors, with the opening width of the annular mesh set to 52 mm.

[0105] On a traction conveyor on the water surface, the molten resin is discharged in lines, causing the continuous lines to fall and bend to form loops, fusing the contact parts and forming a three-dimensional mesh structure. The molten three-dimensional mesh structure is clamped on both sides by the traction conveyor and introduced into cooling water at a traction speed of 2.24 m / min to solidify. Solidification flattens both sides in the thickness direction. Next, it is cut to a specified size and heat-treated with 110°C hot air for 15 minutes to obtain the three-dimensional mesh structure.

[0106] In the obtained three-dimensional network structure, the average fiber diameter of the epidermal layer is 0.81 mm, and the average fiber diameter of the inner layer is 0.89 mm. Furthermore, the fibers in the epidermal layer have a cylindrical cross-section with a hollow section ratio of 42%, while the fibers in the inner layer have a cylindrical cross-section with a hollow section ratio of 40%. The apparent density of the obtained three-dimensional network structure is 0.031 g / cm³. 3 The surface layer density ratio is 0.94, and the thickness is 49 mm. The resulting three-dimensional mesh structure has a hardness of 119.4 N at 25% compression and 205.6 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 1.

[0107] <Comparative Example 2>

[0108] Nine rows of nozzles are arranged along the thickness direction on the effective surface of the nozzle, which has a width length of 97 cm and a thickness length of 62.4 mm. The nozzles are configured as hollow orifices with a triple-bridge shape, having an outer diameter of 5.0 mm and an inner diameter of 4.4 mm. The orifices in the first to ninth rows are arranged in an alternating pattern with a width spacing of 9.0 mm and a thickness spacing of 7.8 mm. The single-orifice discharge ratio is set to 1.0, and the traction speed is set to 1.98 m / min. Otherwise, the process is the same as in Example 4 to obtain a three-dimensional mesh structure. It should be noted that Comparative Example 2 does not distinguish between nozzles for forming the outer skin layer and nozzles for forming the inner layer. For convenience, the single-orifice discharge ratio is recorded as 1.0.

[0109] In the obtained three-dimensional network structure, the average fiber diameter of the epidermal layer is 0.88 mm, and the average fiber diameter of the inner layer is 0.84 mm. Furthermore, the fibers in the epidermal layer have a cylindrical cross-section with a hollow section ratio of 32%, while the fibers in the inner layer have a cylindrical cross-section with a hollow section ratio of 31%. The apparent density of the obtained three-dimensional network structure is 0.035 g / cm³. 3 The surface layer density ratio is 1.26, and the thickness is 50 mm. The resulting three-dimensional mesh structure has a hardness of 118.0 N at 25% compression and 203.0 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 1.

[0110] <Example 5>

[0111] Ten rows of nozzles are arranged along the thickness direction on the effective surface of a nozzle with a width length of 97 cm and a thickness length of 70.2 mm. The nozzles are designed as hollow orifices with a triple-bridge shape, each with an outer diameter of 5.0 mm and an inner diameter of 4.4 mm. The first to tenth rows are arranged in an alternating pattern with a spacing of 9.0 mm between orifices in the width direction and 7.8 mm between orifices in the thickness direction. The average single-orifice discharge rate is set to 4.6 g / min, and the single-orifice discharge rate ratio is set to 1.0. A water tank is positioned with the cooling water surface 40 cm below the nozzle surface. The opening width of the annular mesh is set to 62 mm, and the traction speed is set to 2.13 m / min. Otherwise, the process is the same as in Example 1, resulting in a three-dimensional mesh structure. It should be noted that Example 5 does not distinguish between nozzles for forming the outer skin layer and nozzles for forming the inner layer; for convenience, the single-orifice discharge rate ratio is recorded as 1.0.

[0112] In the obtained three-dimensional network structure, the average fiber diameter of the epidermal layer is 0.65 mm, and the average fiber diameter of the inner layer is 0.63 mm. Furthermore, the fibers in the epidermal layer have a cylindrical cross-section with a hollow section ratio of 36%, while the fibers in the inner layer have a cylindrical cross-section with a hollow section ratio of 34%. The apparent density of the obtained three-dimensional network structure is 0.035 g / cm³. 3 The surface layer density ratio is 0.93, and the thickness is 59 mm. The resulting three-dimensional mesh structure has a hardness of 148.2 N at 25% compression and 261.0 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 1.

[0113] <Comparative Example 3>

[0114] Eleven rows of nozzles were arranged along the thickness direction on the effective surface of the nozzle, which had a width length of 97 cm and a thickness length of 77.9 mm. The nozzles were configured as hollow orifices with a triple-bridge shape, having an outer diameter of 5.0 mm and an inner diameter of 4.4 mm. The first to eleventh rows were arranged in an alternating pattern with an orifice spacing of 9.0 mm in the width direction and 7.8 mm in the thickness direction. The average single-orifice discharge rate was set to 4.1 g / min. A water tank was positioned with the cooling water surface 37 cm below the nozzle surface. The traction speed was set to 1.91 m / min. Otherwise, the process was the same as in Example 5, resulting in a three-dimensional mesh structure. It should be noted that Comparative Example 3 did not distinguish between nozzles for forming the outer skin layer and nozzles for forming the inner layer; for convenience, the single-orifice discharge rate ratio is recorded as 1.0.

[0115] In the obtained three-dimensional network structure, the average fiber diameter of the epidermal layer is 0.68 mm, and the average fiber diameter of the inner layer is 0.66 mm. Furthermore, the fibers in the epidermal layer have a cylindrical cross-section with a hollow section ratio of 32%, while the fibers in the inner layer have a cylindrical cross-section with a hollow section ratio of 31%. The apparent density of the obtained three-dimensional network structure is 0.039 g / cm³. 3 The surface layer density ratio is 1.31, and the thickness is 59 mm. The resulting three-dimensional mesh structure has a hardness of 147.2 N at 25% compression and 259.8 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 1.

[0116] <Example 6>

[0117] Resin C is melted and discharged below the nozzle surface equipped with discharge nozzles. The nozzles are arranged in 10 rows along the thickness direction on the effective surface of the nozzle, which has a width length of 97 cm and a thickness length of 70.2 mm. The nozzles are configured as hollow orifices with a triple-bridge shape, having an outer diameter of 5.0 mm and an inner diameter of 4.4 mm. The first to tenth rows are arranged in an alternating pattern with an orifice spacing of 9.0 mm in the width direction and 7.8 mm in the thickness direction. The resin discharged from the nozzles in the first, second, ninth, and tenth rows in the thickness direction forms the outer skin layer, while the resin discharged from the nozzles in the third to eighth rows in the thickness direction forms the inner layer.

[0118] Molten resin C is discharged below the nozzle surface at a spinning temperature (melt temperature) of 240℃, an average single-hole discharge rate of 3.9 g / min, and a single-hole discharge rate ratio of 2.1. Below the nozzle surface, a water tank is positioned with the cooling water surface 33 cm below the nozzle surface of the discharge nozzle. A pair of traction conveyors are arranged within the water tank, with a portion protruding above the water surface. The traction conveyors have a 150 cm wide stainless steel annular mesh, arranged parallel to the width direction of the nozzle surface and the traction conveyors, with the opening width of the annular mesh set to 58 mm.

[0119] On a traction conveyor on the water surface, the molten resin is discharged in lines, causing the continuous lines to fall and bend to form loops, fusing the contact parts and forming a three-dimensional mesh structure. The molten three-dimensional mesh structure is clamped on both sides by the traction conveyor and introduced into cooling water at a traction speed of 2.51 m / min to solidify. Solidification flattens both sides in the thickness direction. Then, it is cut to a specified size and heat-treated with 90°C hot air for 20 minutes to obtain the three-dimensional mesh structure.

[0120] In the obtained three-dimensional network structure, the average fiber diameter of the epidermal layer is 0.70 mm, and the average fiber diameter of the inner layer is 0.82 mm. Furthermore, the fibers in the epidermal layer have a cylindrical cross-section with a hollow section ratio of 16%, while the fibers in the inner layer have a cylindrical cross-section with a hollow section ratio of 23%. The apparent density of the obtained three-dimensional network structure is 0.034 g / cm³. 3 The surface layer density ratio is 1.05, and the thickness is 51 mm. The resulting three-dimensional mesh structure has a hardness of 112.8 N at 25% compression and 231.5 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 1.

[0121] <Comparative Example 4>

[0122] The single-hole discharge ratio was set to 1.0, and the traction speed was set to 2.36 m / min. Otherwise, the same operation as in Example 6 was performed to obtain a three-dimensional mesh structure.

[0123] In the obtained three-dimensional network structure, the average fiber diameter of the epidermal layer is 0.84 mm, and the average fiber diameter of the inner layer is 0.81 mm. Furthermore, the fibers in both the epidermal and inner layers have a cylindrical cross-section with a hollow content of 20%. The apparent density of the obtained three-dimensional network structure is 0.037 g / cm³. 3 The surface layer density ratio is 1.50, and the thickness is 51 mm. The resulting three-dimensional mesh structure has a hardness of 113.0 N at 25% compression and 230.0 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 1.

[0124] [Table 1]

[0125]

[0126] <Example 7>

[0127] Resin A is melted and discharged below the nozzle surface equipped with discharge nozzles. The nozzles are arranged in 12 rows along the thickness direction on the effective surface of the nozzle, which has a width length of 97 cm and a thickness length of 57.2 mm. The nozzles are configured with orifices of 1.0 mm in diameter, and the first to 12th rows are arranged in an alternating pattern with an orifice spacing of 6.0 mm in the width direction and 5.2 mm in the thickness direction. The resin discharged from the nozzles in the first, second, eleventh, and twelfth rows in the thickness direction forms the outer skin layer, and the resin discharged from the nozzles in the third to tenth rows in the thickness direction forms the inner layer.

[0128] Molten resin A is discharged below the nozzle surface at a spinning temperature (melt temperature) of 240℃, an average single-hole discharge rate of 1.2 g / min, and a single-hole discharge rate ratio of 1.8. Below the nozzle surface, a water tank is positioned with the cooling water level 22 cm below the nozzle surface of the discharge nozzle. A pair of traction conveyors are positioned within the water tank, with a portion protruding above the water surface. The traction conveyors have a 150 cm wide stainless steel annular mesh, arranged parallel to the width of the nozzle surface and the traction conveyors, with the opening width of the annular mesh set to 40 mm.

[0129] On a traction conveyor on the water surface, the molten resin is discharged in lines, causing the continuous lines to fall and bend to form loops, fusing the contact parts and forming a three-dimensional mesh structure. The molten three-dimensional mesh structure is clamped on both sides by the traction conveyor and introduced into cooling water at a traction speed of 1.76 m / min to solidify. Solidification flattens both sides in the thickness direction. Next, it is cut to a specified size and heat-treated with 110°C hot air for 15 minutes to obtain the three-dimensional mesh structure.

[0130] In the obtained three-dimensional network structure, the fibers in the outer layer have a solid cylindrical cross-section with an average fiber diameter of 0.42 mm, while the fibers in the inner layer also have a solid cylindrical cross-section with an average fiber diameter of 0.46 mm. The apparent density of the obtained three-dimensional network structure is 0.039 g / cm³. 3 The surface layer density ratio is 1.10, and the thickness is 37 mm. The resulting three-dimensional mesh structure has a hardness of 70.8 N at 25% compression and 142.3 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 2.

[0131] <Comparative Example 5>

[0132] The single-hole discharge ratio was set to 1.0, and the traction speed was set to 1.60 m / min. Otherwise, the process was carried out in the same manner as in Example 7 to obtain a three-dimensional mesh structure.

[0133] In the obtained three-dimensional network structure, the fibers in the outer layer have a solid cylindrical cross-section with an average fiber diameter of 0.47 mm, while the fibers in the inner layer also have a solid cylindrical cross-section with an average fiber diameter of 0.44 mm. The apparent density of the obtained three-dimensional network structure is 0.043 g / cm³. 3 The surface layer density ratio is 1.48, and the thickness is 38 mm. The resulting three-dimensional mesh structure has a hardness of 72.2 N at 25% compression and 141.0 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 2.

[0134] <Example 8>

[0135] Resin B is melted, and the molten resin A is discharged below the nozzle surface equipped with a discharge nozzle. The nozzles are arranged in eight rows along the thickness direction on the effective surface of the nozzle, which has a width length of 97 cm and a thickness length of 54.56 mm. The nozzles are orifices with a diameter of 1.0 mm, and in rows 1 to 8, they are arranged in an alternating pattern with an orifice spacing of 9.0 mm in the width direction and 7.8 mm in the thickness direction. The resin discharged from the nozzles in rows 1, 2, 7, and 8 in the thickness direction forms the outer skin layer, and the resin discharged from the nozzles in rows 3 to 6 in the thickness direction forms the inner layer.

[0136] Molten resin B is discharged below the nozzle surface at a spinning temperature (melt temperature) of 200°C, an average single-hole discharge rate of 3.5 g / min, and a single-hole discharge rate ratio of 2.0. Below the nozzle surface, a water tank is positioned with the cooling water level 25 cm below the nozzle surface of the discharge nozzle. A pair of traction conveyors are positioned within the water tank, with a portion protruding above the water surface. The traction conveyors have a 150 cm wide stainless steel annular mesh, arranged parallel to the width of the nozzle surface and the traction conveyors, with the opening width of the annular mesh set to 45 mm.

[0137] On a traction conveyor on the water surface, the molten resin is discharged in lines, causing the continuous lines to fall and bend to form loops, fusing the contact parts and forming a three-dimensional mesh structure. The molten three-dimensional mesh structure is clamped on both sides by the traction conveyor and introduced into cooling water at a traction speed of 1.50 m / min to solidify. Solidification flattens both sides in the thickness direction. Then, it is cut to a specified size and heat-treated with 90°C hot air for 20 minutes to obtain the three-dimensional mesh structure.

[0138] In the obtained three-dimensional network structure, the fibers in the outer layer have a solid cylindrical cross-section with an average fiber diameter of 0.76 mm, while the fibers in the inner layer also have a solid cylindrical cross-section with an average fiber diameter of 0.88 mm. The apparent density of the obtained three-dimensional network structure is 0.048 g / cm³. 3 The surface layer density ratio is 1.12, and the thickness is 43 mm. The resulting three-dimensional mesh structure has a hardness of 189.5 N at 25% compression and 305.1 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 2.

[0139] <Comparative Example 6>

[0140] The single-hole discharge ratio was set to 1.0, and the traction speed was set to 1.38 m / min. Otherwise, the operation was the same as in Example 8 to obtain a three-dimensional mesh structure.

[0141] In the obtained three-dimensional network structure, the fibers in the outer layer have a solid cylindrical cross-section with an average fiber diameter of 0.88 mm, while the fibers in the inner layer also have a solid cylindrical cross-section with an average fiber diameter of 0.86 mm. The apparent density of the obtained three-dimensional network structure is 0.052 g / cm³. 3 The surface layer density ratio is 1.35, and the thickness is 43 mm. The resulting three-dimensional mesh structure has a hardness of 189.0 N at 25% compression and 306.7 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 2.

[0142] <Example 9>

[0143] Resin A was used instead of resin B. The spinning temperature (melting temperature) was set to 240°C, the average single-hole discharge rate was set to 2.5 g / min, the water tank was configured such that the cooling water surface was 32 cm below the nozzle surface, the traction speed was set to 1.23 m / min, and the heat treatment was performed for 15 minutes using hot air at 110°C. Otherwise, the process was the same as in Example 8 to obtain a three-dimensional mesh structure.

[0144] In the obtained three-dimensional network structure, the fibers in the outer layer have a solid cylindrical cross-section with an average fiber diameter of 0.38 mm, while the fibers in the inner layer also have a solid cylindrical cross-section with an average fiber diameter of 0.41 mm. The apparent density of the obtained three-dimensional network structure is 0.042 g / cm³. 3 The surface layer density ratio is 1.10, and the thickness is 43 mm. The resulting three-dimensional mesh structure has a hardness of 132.2 N at 25% compression and 250.9 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 2.

[0145] <Comparative Example 7>

[0146] The single-hole discharge ratio was set to 1.0, and the traction speed was set to 1.10 m / min. Otherwise, the process was carried out in the same manner as in Example 9 to obtain a three-dimensional mesh structure.

[0147] In the obtained three-dimensional network structure, the fibers in the outer layer have a solid cylindrical cross-section with an average fiber diameter of 0.42 mm, while the fibers in the inner layer also have a solid cylindrical cross-section with an average fiber diameter of 0.38 mm. The apparent density of the obtained three-dimensional network structure is 0.047 g / cm³. 3 The surface layer density ratio is 1.35, and the thickness is 43 mm. The resulting three-dimensional mesh structure has a hardness of 135.0 N at 25% compression and 257.3 N at 50% compression. The manufacturing conditions and the physical properties of the obtained three-dimensional mesh structure are summarized in Table 2.

[0148] [Table 2]

[0149]

[0150] The three-dimensional mesh structures in Examples 1-3 all had the same thickness and the same compressive hardness as the three-dimensional mesh structure in Comparative Example 1, and the apparent density in Comparative Example 1 was 0.038 g / cm³. 3 In contrast, the concentration in Examples 1-3 was 0.033-0.035 g / cm³. 3 Therefore, it can be seen that in Examples 1 to 3, although the apparent density was reduced by 8 to 13% compared with the three-dimensional mesh structure of Comparative Example 1, resulting in weight reduction, a three-dimensional mesh structure with the same degree of compressive hardness was obtained.

[0151] The same applies between Example 4 and Comparative Example 2, Example 5 and Comparative Example 3, Example 6 and Comparative Example 4, Example 7 and Comparative Example 5, Example 8 and Comparative Example 6, and Example 9 and Comparative Example 7. In these examples, although the apparent density was reduced by about 10% compared with the three-dimensional mesh structure of the corresponding comparative example, a three-dimensional mesh structure with the same degree of compressive stiffness was obtained.

[0152] Industrial availability

[0153] The three-dimensional mesh structure of the present invention is suitable for use as a cushioning component. Cushioning components can be used for applications requiring elasticity to support objects, applications requiring impact reduction, etc., such as office chairs, furniture, sofas, beds and other bedding, and vehicle seats for trams, automobiles, and motorcycles.

Claims

1. A three-dimensional mesh structure, characterized in that, It is composed of continuous lines and has a three-dimensional random ring joint structure, wherein the continuous lines are composed of a thermoplastic resin composition. Both surfaces of the three-dimensional mesh structure in the thickness direction are skin layers, and the apparent density of the skin layer divided by the apparent density of the three-dimensional mesh structure is less than 1.

25.

2. The three-dimensional mesh structure according to claim 1, wherein, The three-dimensional mesh structure has an inner layer sandwiched between two epidermal layers, and the average fiber diameter of the lines constituting the epidermal layer and the inner layer is 0.1 mm to 3.0 mm.

3. The three-dimensional mesh structure according to claim 2, wherein, The apparent density of the three-dimensional mesh structure is 0.01 g / cm³. 3 ~0.20g / cm 3 The apparent density of the epidermis is 0.01 g / cm³. 3 ~0.20g / cm 3 .

4. The three-dimensional mesh structure according to claim 3 has a thickness of 10~300mm.

Citation Information

Patent Citations

  • Antivirus fiber and antivirus fabric

    JP2024052441A

  • Elastic network structure exhibiting excellent lightweightness and hardness

    WO2014192790A1